Desa Anti Politik Uang (Money Politik) sebagai Strategi Antisipasi Pilkada Curang Tahun 2024 Provinsi Gorontalo - Jupri Jupri; Suardi Rais; Haritsa Haritsa; Aliyas Aliyas; Rommy Yusuf Hiola (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The village is the smallest entity with its strategic position in holding regional elections which is vulnerable to the practice of money politics. Project mark ups, vote buying, bribery, gratuities constitute political corruption when elected as leader. The impact of the regional elections is that they do not produce authentic leaders for the welfare of their citizens. The aim of the research is to build an anti-money politics village as a strategy to anticipate fraudulent regional elections in 2024. This research uses a socio-legal research approach with literature study techniques and in-depth interviews. The research results show that the practice of money politics is influenced by several factors and to minimize these factors, an anti-money politics village model must be formed, one of which is through literacy or community forum-based education.